Various outcomes of Idiopathic Grade IV Intraventricular Haemorrhage in term newborns at two years of age. (Bangladesh Journal of Medical Science, 2018)
Abstract not availableBangladesh Journal of Medical Science Vol.17(2) 2018 p.316-318